Odpowiedzi

2009-12-14T19:43:16+01:00
E) 4x+5y=12,3/*3
3x-2y=-4/*-4
12x+15y= 36,9
-12x+8y=16
12x-12x+15y+8y=36,9+16
23y=52,9
y=2.3
4x+5*2,3=12,3
4x=12,3-11,5
4x=0,8
x=0,2
f) 3x-0,2y=35/*2,5
2,5x-5y=5/*-3
7,5x-0,5y=87,5
-7,5x+15y=-15
7,5x-0,5y-7,5x+15y=87,5-15
14,5y=72,5
y=5
3x-1=36
x=12
2009-12-14T19:56:56+01:00
D) 5v₁ + 4v₂ = 4 | × (-7)
7v₁ + 5v₂ = 6 | × 5

-35v₁ - 28v₂ = -28
35v₁ + 25v₂ = 30

-3v₂ = 2 | : (-3)
v₂ = ⅔


5v₁ + 4v₂ = 4 | × (-5)
7v₁ + 5v₂ = 6 | × 4

-25v₁ - 20v₂ = -20
28v₁ + 20v₂ = 24

3v₁ = 4 | : 3
v₁ = 1⅓

_________________

v₁ = 1⅓
v₂ = ⅔
_________________




e) 4x + 5y = 12,3 | × (-3)
3x - 2y = -4 | × 4

-12x - 15y = -36,9
12x - 8y = -16

-23y = -52,9 | : (-23)
y = 2,3


4x + 5y = 12,3 | × 2
3x - 2y = -4 | × 5

8x + 10y = 24,6
15x - 10y = -20

23x = 4,6 | : 23
x = 0,2

_________________

x = 2,3
y = 0,2
_________________




f) 3x - 0,2y = 35 | × (-2,5)
2,5x - 5y = 5 | × 3

-7,5x + 0,5y = -87,5
7,5x - 15y = 15

-14,5y = -72,5 | : -14,5
y = 5


3x - 0,2y = 35 | × (-5)
2,5x - 5y = 5 | × 0,2

-15x + y = -175
0,5x - y = 1

-14,5x = -174 | : (-14,5)
x = 12

_________________

x = 12
y = 5
_________________